Assessing impact of urban street infrastructure on pedestrian safety perception. Issue 2 (20th May 2021) - Hussain, Md Saddam; Kumari, Ranjana; Nimesh, Vikas; Goswami, Arkopal Kishore
Abstract : Pedestrian road safety needs urgent attention as it causes a growing number of vulnerable road users in traffic accidents. Significant factors that lead to vehicular crashes may include vehicle speed, road design and driver behaviour. However, in India, 14% of the total road fatalities in 2017 involved pedestrians, and research is scarce in this domain. Behaviour of pedestrians play a role in understanding crash risk, and such behaviour is likely governed by attitudes and perceptions that pedestrians have regarding the walking environment. This paper develops a relationship among pedestrian's perception of safety and associated factors by collecting random samples of approximately 1600 pedestrians in three Indian cities of Varanasi, Jaipur and Hyderabad. City-specific as well as aggregate ordinal logit models were developed to estimate the overall safety perception of pedestrians. The results reveal that perception regarding factors such as buffer, ease of walking, unsafe driving practices, and poor infrastructure condition and maintenance significantly affect pedestrians' safety perception across all three cities. In parallel, there are perception factors that are city-specific, including satisfaction with nighttime safety, zebra crossings and footpath continuity. These results provide the decision makers with a direction to develop mitigation strategies that likely would enhance pedestrian safety.